Evaluation of diagnostic tools and fertilizer sources for phosphorus and sulfur management in winter wheat - Weber, Christopher M. (Kansas State University, 2021)
Three studies were conducted to assess winter wheat (Tritticum aestivum) response to phosphorus (P) and sulfur (S) and evaluate soil test methods and tissue tests as diagnostic tools. The first study compared different commercially available soil test P methods in Kansas soils. This study was performed on 24 locations in 2019 and 2020. It was designed to include various soils across the wheat-growing regions of Kansas, and locations were selected based on initial soil test P concentrations. Fertilizer treatments included pre-plant broadcast P fertilizer at rates of 0, 45, 90, and 135 kg of P₂O₅ ha⁻¹. Soil samples were collected at the 0-15 cm depth and analyzed using six soil test P methods. Results from this study found that most soil test P (STP) methods correlate well with the Mehlich-3 (M3) method. The highest correlation was with the Bray-1 (B1), while the lowest was with the H3A. The B1 and H3A method correlations to the M3 method were affected by high soil pH and calcium carbonate. Critical STP levels for winter wheat differed between STP methods. The lowest critical level for wheat grain yield was 12.2 mg of P kg⁻¹ for the Olsen test, while the highest was 36.7 mg of P kg⁻¹ with the Mehlich-3 ICP test. The second study evaluated soil test S methods and wheat response to sulfate and elemental S fertilizer sources. Sulfur application rates included 0, 11, and 45 kg of S ha⁻¹, and all plots received a balanced blanket application of N and P fertilizer. Profile soil samples (0-30 and 30-60 cm) were taken before fertilization and tested with four different S soil test methods. Plant tissue samples were collected at the Feekes 6 growth stage, and flag leaf samples were collected at the Feekes 10.5 growth stage. Results from this study indicate that the four sulfur soil test methods had a wide range of correlations indicating that different methods could be extracting S from different sulfur pools of S in the soil. When comparing these methods, the calcium phosphate and ammonium acetate methods correlated the best between all method comparisons to one another. When analyzing tissue S concentration, S rates had the biggest impact while the source of S had limited response at any location. The third study evaluated the effects of blending P fertilizer with winter wheat seed prior to drilling. Treatments included a factorial combination of two P fertilizer sources, three P rates, and four storage times of the seed-fertilizer blend prior to drilling. Four locations were established in 2019 and 2020. Fertilizer sources included diammonium phosphate (DAP) and MESZ; rates included 34, 67, and 135 kg of P₂O₅ ha⁻¹; and blend storage times of 0, 7, 22, and 34 days. Results from this study found that the blend storage time and fertilizer source had limited impacts on winter wheat NDVI, P uptake, biomass, and grain yield responses in the field. P fertilizer rate had the biggest impact on NDVI, P uptake, biomass and grain yield responses and was the biggest response in this study which was likely due to locations being lower in P compared to general guidelines.
Keywords: Winter wheat; Phosphorus fertility; Sulfur fertility